NILAI-NILAI ISLAM DALAM BUDAYA ADAT KIRAB PUSOKO SAMPURING SELO RECO DI DESA NGRECO KABUPATEN PACITAN - Ismail; Romelah; Humaidi , Nurul (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study aims to explore the essence of the traditional ceremony of Kirab Pusaka Sampur Selo Reco in the village of Ngreco, Pacitan Regency, from the perspective of the values of Al-Islam Kemuhammadiyahan. The research utilizes a qualitative approach with the intention to preserve the form and content of the actions and analyze their quantities to be transformed into qualitative entities. The research method used is phenomenology. The research sample is taken using purposive sampling techniques, involving the participants in the traditional ceremony. Data collection is carried out through interviews, documentation, and literature review. The results of this study indicate that the traditional ceremony of Kirab Pusoko Sampuring Selo Reco in Desa Ngreco, Pacitan Regency, emphasizes the perspective of the values of Al-Islam Kemuhammadiyahan. Overall, the study examines how traditional customs, Islamic values, and Javanese culture synergize in the context of the Kirab Pusoko Sampuring Selo Reco ceremony in Desa Ngreco, while highlighting Muhammadiyah's efforts to integrate and rationalize these values in modern life. Keywords: Muhammadan Islam; Cultural Parade.